Evaluation of a new "all in one" SARS‐CoV‐2 antigen‐detecting rapid diagnostic test and self‐test: Diagnostic performance and usability in child and adult populations. Issue 9 (25th May 2022) - Prazuck, Thierry; Gravier, Anne; Pires‐Roteira, Daniela; Theillay, Aurelie; Pallay, Sandra; Colin, Mathilda; Serreau, Raphael; Hocqueloux, Laurent; Cassuto, Nino Guy
Abstract: The control of the COVID‐19 epidemics has been one global health priorities for the last 2 years. To that end, more reliable and easy‐to‐use, regardless of age, diagnostic tests are necessary. Considering that, we evaluated an innovative two‐step self‐test, the AAZ COVID‐VIRO ALL IN®, switching from the classic nasal swab to a nasal sponge. We performed a multicenter study, on 124 adults and children, in a point‐of‐care setting. Sensitivity, specificity and overall acceptance of the COVID‐VIRO ALL IN® self‐test compared to reverse transcriptase polymerase chain reaction (RT‐PCR) on nasopharyngeal samples were of 93.0%, 100%, and 97.5%, respectively. We then performed a multicenter, usability study to evaluate the ease of use of COVID‐VIRO ALL IN® on 68 laypersons adults. A vast majority of participants correctly executed and interpreted the test. The usability was then specifically investigated on 40 children and teenagers, comparing COVID‐VIRO® first generation to the new COVID‐VIRO ALL IN®. They all found COVID‐VIRO ALL IN® more comfortable and easier to use. For young children, the new self‐test seems safer (less risk of trauma and no liquid exposure), and faster than saliva‐based RT‐PCR. Moreover, the COVID‐VIRO ALL IN® can easily be adapted as a multiplex self‐test for other respiratory viruses, opening new perspectives of simultaneous, rapid and massive detection of respiratory infections, especially among vulnerable populations like children and elderly people.